1998
DOI: 10.1086/300362
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Blue Stragglers Formed via Stellar Collisions

Abstract: We have used the results of recent smoothed particle hydrodynamic simulations of colliding stars to create models appropriate for input into a stellar evolution code. In evolving these models, we Ðnd that little or no surface convection occurs, precluding angular momentum loss via a magnetically driven stellar wind as a viable mechanism for slowing rapidly rotating blue stragglers that have been formed by collisions. Angular momentum transfer to either a circumstellar disk (possibly collisional ejecta) or a ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Sandquist, Bolte and Hernquist (1997) find similar results. However, subsequent convection or meridional circulation can still induce mixing (Leonard & Livio 1995;Lombardi et al 1995), although this was not found to be the case in detailed numerical work by Sills et al (1997) and Ouellette & Pritchet (1998). In summary, "absence of proof is not proof of absence"; if the analogy to blue stragglers is justified, then it appears that the lack of unusual spectral features in the S-stars does not place strong constraints on their origin.…”
Section: The Riddle Of the Young Starsmentioning
confidence: 93%
“…Sandquist, Bolte and Hernquist (1997) find similar results. However, subsequent convection or meridional circulation can still induce mixing (Leonard & Livio 1995;Lombardi et al 1995), although this was not found to be the case in detailed numerical work by Sills et al (1997) and Ouellette & Pritchet (1998). In summary, "absence of proof is not proof of absence"; if the analogy to blue stragglers is justified, then it appears that the lack of unusual spectral features in the S-stars does not place strong constraints on their origin.…”
Section: The Riddle Of the Young Starsmentioning
confidence: 93%
“…-Modelling of collisional blue stragglers in globular clusters (Sills & Bailyn 1999): the number and distribution of the stragglers in the colour-magnitude diagrams are determined by the current dynamical state and population of the clusters. More analyses of the formation of, and mixing in, collisional globular-cluster stragglers: Sills et al (1995), Sandquist et al (1997), Ouellette & Pritchet (1998), Lombardi et al (2002). -Discussion of high-resolution spectra of stragglers in M 67 (Shetrone & Sandquist 2000): the abundance of CNO elements may be a better index for distinguishing collisional stragglers from those resulting from mass transfer in close binaries.…”
Section: Theoriesmentioning
confidence: 99%
“…As previously observed, the BSs tend to reside redward of the ZAMS. Ouellette & Pritchet (1998) and Ouellette (2000) simulated different synthetic BS populations using a range of assumptions for their creation scenarios. By comparing the positions of these synthetic populations to those of the real populations in several clusters they deduced the most likely BS formation scenario.…”
Section: Comparison With Stellar Evolutionary Modelsmentioning
confidence: 99%